The Influence of Mobile-Based and Web-Based Management Applications on School Administrative Efficiency in Public Elementary Schools - Anggun Fauziana Kusumastuti; Achmad Buchori; Fakhruddin Fakhruddin (Jurnal Ragam Pengabdian, 2026)
Digital transformation in education has encouraged schools to adopt information technology to improve administrative efficiency. However, implementing digital-based management applications in elementary schools still faces challenges related to technology utilization, user readiness, and process optimization. This study aims to analyze the effects of mobile-based and web-based management applications on school administrative efficiency in public elementary schools in Jumo District, Temanggung Regency. A quantitative approach with an ex post facto design was employed, involving 90 teachers selected through proportional random sampling from a population of 117 teachers across 14 public elementary schools. Data were collected using a Likert-scale questionnaire and analyzed using simple and multiple linear regression with SPSS. The results show that both mobile-based and web-based management applications have a positive and significant effect on school administrative efficiency, and their simultaneous use also significantly influences administrative efficiency. These findings indicate that digital management applications enhance administrative effectiveness through faster information access, systematic data management, and more efficient administrative processes. This study implies that elementary schools need to strengthen digital transformation strategies by optimizing technology utilization and improving users' digital competencies.